2021
DOI: 10.1177/11786329211036855
|View full text |Cite
|
Sign up to set email alerts
|

Use of Project ECHO Telementoring Model in Continuing Medical Education for Pediatricians in Vietnam: Preliminary Results

Abstract: The ECHO (Extension for Community Health Outcomes) model has been introduced and implemented in several hospitals and health programs in Vietnam since 2015. In 2018, Vietnam National Children’s Hospital (VNCH) officially implemented the ECHO model to provide continuing medical education (CME) credits on pediatrics topics for medical staff in its satellite hospitals and health centers in the Northern region of Vietnam. This paper presents preliminary results of the ECHO program at VNCH. Methods included pre- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The ECHO model has been widely adopted in 49 countries as of 2020 across 6 continents, with 528 hubs and 955 different programs covering disease conditions, such as rheumatology, dermatology, musculoskeletal disease, asthma, chronic pain, diabetes, epilepsy, hypertension, liver disease, mental health, HIV, geriatric, COVID19 among others [16] . In Uganda, Seed Global Health and the Ministry of Health applied this approach to the emergency medical services, the first on the African continent and we evaluated its impact for a pilot period of 6 months and also provide an account of its establishment as a benchmark for other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The ECHO model has been widely adopted in 49 countries as of 2020 across 6 continents, with 528 hubs and 955 different programs covering disease conditions, such as rheumatology, dermatology, musculoskeletal disease, asthma, chronic pain, diabetes, epilepsy, hypertension, liver disease, mental health, HIV, geriatric, COVID19 among others [16] . In Uganda, Seed Global Health and the Ministry of Health applied this approach to the emergency medical services, the first on the African continent and we evaluated its impact for a pilot period of 6 months and also provide an account of its establishment as a benchmark for other countries.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the continuous learning applied the ECHO model had improved the capacity of HIV healthcare workers in Vietnam a great deal that 90% of participants wanted to participate in the next courses [ 7 ]. Another study also indicated that the pediatric care providers improved their professional knowledge and skill after following Project ECHO training [ 15 , 22 ]. Our findings are consistent with those from other settings [ 4 , 13 , 14 , 24 26 ], and again show the potential of the ECHO model in improving knowledge for medical staff at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies about Project ECHO that applied for pediatrics [ 15 ]. We implemented the Project ECHO for pediatricians to expand the expertise knowledge in some faculties related to pediatrics, including Neonatology, Pediatric respiratory diseases, Pediatric Cardiology, to the distant area throughout Vietnam [ 22 ]. Thanks to the IT innovation recently in Vietnam, especially in the condition of Covid-19 pandemic spreading, the distance learning has become more urgent than ever before to satisfy the social demands of distancing that have attracted a large number of participants to join.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telementoring provides a platform for professionals with specific content knowledge and expertise within a particular organisation/context to collaborate, share and empower colleagues internally and externally (Agley et al, 2021 ; Bachynsky, 2020 ; Barbera et al, 2017 ; Christian & Andreas, 2019 ; Gegenfurtner & Ebner, 2019 ; Hauer & Quill, 2011 ). The virtual nature of telementoring overcomes traditional boundaries of geography, sector, professional discipline and seniority, and other siloes to integrate the way workforces can learn, seek advice and support, and consequently use newly acquired knowledge to enhance their service provision capabilities (Arora et al, 2020 ; De Witt Jansen et al, 2018 ; Gleason et al, 2020 ; Joshi et al, 2020 ; Katzman et al, 2020 , 2021a , 2021b ; Lewiecki et al, 2017 ; McPhillips et al, 2021 ; Nhung et al, 2021 ; Tosi et al, 2020 ). While telementoring is not a new concept, the contemporary implementation of telementoring models such as Project ECHO is a disruptive innovation which effects change within the organisation adopting the model for the first time.…”
Section: Introductionmentioning
confidence: 99%